Design, Fabrication, and Testing of Salt Spray as An Atmospheric Corrosion Test Tool Using MgCl₂ and NaCl Solutions - Sri Hastuty; Darius Tegar Oktaviyanto; Fatwa Khoirrun Nadhor; Wahyu Caesarendra; Muhammad Awwaluddin (Jurnal Kimia Sains dan Aplikasi, 2024)
The research aimed to design a salt spray chamber adhering to ASTM-B117 standards and test the chamber with determine the atmospheric corrosion rate in a salt spray chamber using steel materials (ST 37 and SS 304) in NaCl and MgCl2 solutions. Corrosion tests spanned 48 hours, with time variables of 4, 6, and 8 hours of wet and dry cycle for 48 hours total. The objective was to design salt spray chamber and test the chamber to compare the corrosion rate based on solution and material selected. Visual inspections post-corrosion included macro photos, microscopy, SEM, and EDS analyses. Weight loss in Steel ST 37, cleaned per ASTM G1 with HCl, was also assessed. Corrosion rates of Steel ST 37 varied marginally across time variables and solutions. NaCl corrosion rates at 4, 6, and 8 hours averaged 4.5232, 5.8418, and 6.7148 mmpy, respectively. For MgCl2, rates were 4.2564, 5.3436, and 6.0915 mmpy, respectively. Stainless steel exhibited higher resistance compared to Steel ST 37. In conclusion, both NaCl and MgCl2 solutions accelerate corrosion, with NaCl inducing a higher rate. Stainless steel outperforms Steel ST 37, and the chamber material displays resilience against atmospheric corrosion.